Interaction between temperature and photoperiod on growth and feeding of Atlantic cod ( Gadus morhua ): possible secondary effects - Imsland, Albert Kjartansson; Foss, Atle; Alvseike, Thomas; Folkvord, Arild; Stefansson, Sigurd Olav; Jonassen, Thor Magne (Canadian Journal of Fisheries and Aquatic Sciences, 2007)
Interactions between temperature and photoperiod on growth of Atlantic cod (Gadus morhua) juveniles (initial weight 9.1 g) were studied by rearing juvenile cod 3 months under simulated natural photoperiod (LDN) and continuous light (LD24:0) at 7, 10, and 13 °C. Juvenile Atlantic cod exposed to LD24:0 had higher growth rate and better feed conversion efficiency compared with cod reared under LDN. Optimal temperature for growth of juvenile Atlantic cod in the size range 5–50 g was influenced by photoperiod and was estimated to be 12.3 °C under LD24:0 and 15.7 °C under LDN. After termination of the laboratory study, the fish were reared in sea pens at ambient conditions for 17 months. The growth-enhancing effect of LD24:0 could be traced far beyond the duration of the laboratory trial, as the final mean weights in June 2005 of the fish reared at LD24:0 and 13 and 10 °C in the laboratory trial were 8% and 13% higher than those of the respective LDN groups. Our study indicates a physiological mechanism that might be linked to cod migrations, as maximal growth and feeding efficiency will be attained in areas during a season with extended day length or continuous light.